Analysis of Service Quality in Pharmaceutical Installations on Outpatient Patient Satisfaction - Tarigan, Jingkat; Nadapdap, Thomson P; Syamsul, Darwin; Tarigan, Andini Mentari (Newinera Publisher, 2023)
Pharmaceutical services are direct and responsible services to patients relating to pharmaceutical preparations with the aim of achieving definite results to improve the quality of life of patients. The purpose of this study was to analyze the quality of service in the Pharmacy Installation on the satisfaction of outpatients in the Kabanjahe Regional General Hospital. Research conducted is quantitative with cross sectional approach. The study population was all outpatients in the Pharmacy Installation of the Kabanjahe District General Hospital, amounting to 13,359 in November 2018-January 2019. Samples taken were 87 people, obtained using proportional sampling techniques. Data obtained by interview and observation using a questionnaire, analyzed by Multiple Logistic Regression Test at α = 0.05. The results of the multiple logistic statistical tests show that there is a significant influence of the reliability variable (p = 0.023), concern (p = 0.032), direct evidence (p = 0.016) on patient satisfaction. Concern variable gave the greatest influence on patient satisfaction in the Outpatient Pharmacy of the Kabanjahe Regional General Hospital with (Exp value (B) of 146,434). The conclusion of this study is that there is a significant influence on reliability, care and direct evidence on patient satisfaction. It is recommended to the management of the Kabanjahe Regional General Hospital to provide punishment for officers who have not been optimal in providing services and to increase the reliability, care, and direct evidence of officers to improve patient satisfaction.